RIN4-like proteins mediate resistance protein-derived soybean defense against Pseudomonas syringae - Selote, Devarshi (Landes Bioscience, 2010)
Resistance (R) protein mediated recognition of pathogen avirulence effectors triggers signaling that induces a very robust form of species-specific immunity in plants. The soybean Rpg1-b protein mediates this form of resistance against the bacterial blight pathogen, Pseudomonas syringae expressing AvrB(Pgyrace4). Likewise, the Arabidopsis RPM1 protein also mediates species-specific resistance against AvrB expressing bacteria. RPM1 and Rpg1-b are non-orthologous and differ in their requirements for downstream signaling components. We recently showed that the activation of Rpg1-b derived resistance signaling requires two host proteins that directly interact with AvrB. These proteins share high sequence similarity with the Arabidopsis RPM1 interacting protein 4 (RIN4), which is essential for RPM1-derived resistance. The two soybean RIN4-like proteins (GmRIN4a and b) differ in their abilities to interact with Rpg1-b as well as to complement the Arabidopsis rin4 mutation. Because the two GmRIN4 proteins interact with each other, we proposed that they might function as a heteromeric complex in mediating Rpg1-b-derived resistance. Absence of GmRIN4a or b enhanced basal resistance against bacterial and oomycete pathogens in soybean. Lack of GmRIN4a also enhanced the virulence of avrB bacteria in plants lacking Rpg1-b. Our studies suggest that multiple RIN4-like proteins proteins mediate R-mediated signaling, in soybean.